Β-2-himachalen-6-ol: A novel anticancer sesquiterpene unique to the Lebanese wild carrot. (22nd August 2016) - Taleb, Robin I.; Najm, Paul; Shebaby, Wassim; Boulos, Joelle C.; Demirdjian, Sally; Hariri, Essa; El-Sibai, Mirvat; Daher, Costantine; Mroueh, Mohamad
Abstract: Daucus carota ssp. carota, also known as wild carrot, is a commonly used herb in Lebanese folk medicine to treat several ailments including cancer. Previous studies in our laboratories showed that the Daucus carota oil extract (DCOE) and subsequent fractions exhibit antioxidant, anti-inflammatory and anti-cancer activities. In this study, we report the isolation and identification of the major compound responsible for the anti-cancer activity of DCOE along with the mechanism of action involved. GC–MS and NMR spectroscopy revealed the identity of the major compound as β-2-himachalen-6-ol, a novel sesquiterpene unique to the Lebanese wild carrot. β-2-Himachalen-6-ol demonstrated potent anti-cancer activity against B16F-10, Caco-2, MB-MDA-231, A549 and SF-268 cancer cells (IC50 13–4 µg/ml; 58–18 µM), with SF-268 cells being the most sensitive. The sesquiterpene was shown to induce cell death through apoptosis (flow cytometry), decrease 2D cell motility (wound healing assay) and 3D invasion, as well as increase cell adhesion in SF-268 cells. Additionally, β-2-himachalen-6-ol showed very low toxicity in mice with an LD50 >6000 mg/kg body weight. In conclusion, the present data demonstrate that β-2-himachalen-6-ol is a potential multi-mechanistic chemotherapeutic drug with high potency and safety. Graphical abstract: